The Effect of National Examination and Curriculum on Students’ Performance in Solving TIMSS Model Mathematics Problems - Anwaril Hamidy; J. Jailani; Fathur Rahman (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
This study was aimed to investigate effect of National Examination (UN) and curriculum also their interaction effect on students’ performance in solving TIMSS model Mathematics problems. This study was carried out with 300 8th graders of East Kalimantan students. The participants were from three mathematic National Examination result school categories on 2016 (low, moderate and high) and two implemented curriculum types (KTSP and Currciculum 2013). Data collection used 28 items TIMSS model Mathematics problems (α = 0.837) which contained content and cognitive domain. Data analysis used two ways analysis of variance. Data analysis revealed that there were significance main effect of national examination and curriculums, also interaction  effect between of them on mathematic achievement. There were significance main effect of national examination and curriculums on content domain. But, there was no significance interaction effect between of them on performance in solving geometry. There were significance main effect of national examination and curriculums on cognitive domain. But, there was no significance interaction effect between of them on knowing thinking level.